USING THE TECHNOLOGY OF COLLECTIVE GAME COMMUNICATION IN THE PROCESS OF FORMING THE DIAMONOLOGICAL COMPETENCY OF PRIMARY SCHOOL PUPILS - Lapshyna, Iryna; Lyubchak, Lyudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The authors consider the diamonological competency of primary school pupils as a component of communicative competency, which is defined among other end-results of secondary education in modern Ukraine. They convince that communication for meeting educational, personal and professional demands involves the ability to respond adequately to a partner, a participant of a certain activity. That is, by means of linguistic means a pupil can plan, organize, edit, and monitor the course of action as well as its results. Taking into account the age-specific peculiarities of primary school pupils, the authors consider the technology of collective game communication, integrating the collective game forms and the speech communication, to be very effective for forming their diamonological competency. Correctly organized collective game communication of primary school pupils will not only contribute to the formation of the conscious linguistic personalities with free expression of thoughts, but also to the pupils’ harmonious development and their training for creative self-realization.